A Glance at the Activity of Iranian Researchers and Reviewers in Publons - Nojavan, Fereshteh; Ghasemian, Amir; Asnafi, Amir Reza; Zarei Morad Haseli, Mohammad Javad (DESIDOC Journal of Library & Information Technology, 2022)
Publons is a portal that gives information on scientific products, review activities, and the scientometric standing of researchers. In this line, the present study attempted to evaluate the review actions of researchers of Iranian universities in Publons. In this applied research, the 10 best institutions of Iran were picked as the comprehensive research based on the number of researchers in Publons. Demographic data, verified reviews, and scientometric indicators were extracted. Microsoft Office and R applications were used to examine the data. The findings suggested that the University of Tehran has top rank in terms of verified reviews compared to other institutions. Researchers from Iran University of Science and Technology in Publons did better with high H-index and citations. The data also demonstrated that there was a statistically significant association between scholars’ review activities with research products and scholars’ H-index, according to which the editors-in-chief of journals pick academics who have a lot of reputation and research products for review. Publons is an excellent instrument for researchers to exhibit their scientific strength in evaluating the editors-in-chief of journals in the worldwide community and also raise the quality of publishing research outputs by developing the talent of criticism and review.